2010
DOI: 10.1097/wnr.0b013e328340a77b
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic preconditioning increases gap-junctional graft and host communication

Abstract: Gap-junctional intercellular communication between grafted neural stem cells (NSCs) and host cells seems to be essential for many of the functional and beneficial interactions after NSC engraftment. Gap-junctional communication is also known to increase in the central nervous system after hypoxia and ischemia. We therefore hypothesized that controlled hypoxic preconditioning of murine NSCs (C17.2) before the engraftment is a reliable method to increase connexin 43 expression and improve subsequent graft and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…In terms of functional engraftment, a recent in vitro study by Jaderstad and associates has reported an increased in gap-junctional intercellular communication between hypoxic preconditioned neural stem cells and host cells in vitro, a consequence of increased expression of connexin 43 (Jaderstad et al, 2010). In support of this finding was a previous study reporting that HPC of human MSCs enhanced their xenografting efficiency into chick embryos, a model employed to examine the in vivo engraftment and differentiation potential of stem cells (Hung et al, 2007b).…”
Section: Differentiation and Engraftmentsupporting
confidence: 75%
“…In terms of functional engraftment, a recent in vitro study by Jaderstad and associates has reported an increased in gap-junctional intercellular communication between hypoxic preconditioned neural stem cells and host cells in vitro, a consequence of increased expression of connexin 43 (Jaderstad et al, 2010). In support of this finding was a previous study reporting that HPC of human MSCs enhanced their xenografting efficiency into chick embryos, a model employed to examine the in vivo engraftment and differentiation potential of stem cells (Hung et al, 2007b).…”
Section: Differentiation and Engraftmentsupporting
confidence: 75%
“…Rate of successful engraftment and the differentiation capacity of the preconditioned MSCs are higher than nonpreconditioned controls (Jäderstad et al 2010;Ren et al 2006). Chemotaxis, proliferation, and migration capacities of MSCs are enhanced following their treatment under optimized sub-lethal stress conditions (Liu et al 2010;Tang et al 2009b).…”
Section: Preconditioningmentioning
confidence: 86%
“…The authors linked TRPV4-mediated vascular preservation functions during hypoxic preconditioning to increased gap junction cell communication. Previous reports have linked the protective effects of hypoxic preconditioning to increased gap junctional cell communication [35,43]. Connexins are the core proteins of these channels which interact with other proteins including caveolins to regulate the gap junction intercellular communication [75].…”
Section: Hypoxic Preconditioningmentioning
confidence: 99%